Diabetes unmasked by electric shock. Issue 3 (1st March 2002) - Kane, M; Swift, P G F
Abstract : Following an accidental electric shock, a boy with no previous symptoms developed hyperglycaemia, rapidly evolving into diabetes. He was aglycosuric for 24 hours after the shock. Islet cell antibodies were shown shortly after the accident. Although destined to develop diabetes, it seems likely that the electric shock unmasked impaired glucose tolerance. Glucose homoeostasis should be monitored in children following significant electric shocks.